Design and analysis of voltage clamped bidirectional DC–DC converter for energy storage applications. Issue 7 (21st May 2018) - Narasimharaju, Beeramangalla Lakshminarasaiah; Ramanjaneya Reddy, Udumula; Dogga, Raveendhra
Abstract : The coupled inductor (CI) bidirectional DC–DC (BDC) converters are becoming popular in energy storage applications owing to high range factor, reduced device stress and high efficient. However, the applications of CI‐BDC are limited due to the leakage energy of CI. Hence, this work proposes a voltage‐clamp (VC) CI‐BDC converter that effectively recovers the leakage energy while clamping switch turn‐off voltage spikes, thus, guard the device from high‐voltage stress. The working principle of proposed BDC converter with its characteristic waveforms and the steady‐state analysis is presented. The equivalent circuits are obtained for the each interval operation of CI‐BDC converter with voltage clamp in both boost (discharging) and buck (charging) mode. A Simulink/MATLAB‐based design is presented for the CI‐BDC converter with voltage clamp. A 60 W, prototype of proposed converter has been developed and validated experimentally with the simulation counterparts. To confirm the elimination of leakage energy of CI, the analyses of VC‐CI‐BDC converter are compared with CI‐BDC converter counterparts.